Os mundos de Maracanã: obrigações, medos e transformações urbanas numa região da ilha de São Luís-MA - Alcobaça, Luzinele Everton de (2024)
Previously conceived as a settlement, Maracanã region (Maranhão, Brazil) is now composed by districts considered as rural and outskirts in the relation they establish with the urban centers of the region. Maracanã, Alegria and Vila Mochel share political, historical and cultural specificities concerning their flow of knowledge and people in varied contexts. Between 2013 and 2018, thousands of houses were built in the region through the Brazilian Social Housing Program “Minha Casa Minha Vida”. This was something producing an environmental impact in the swamps, rivers and juçara forests, in addition to producing a tension in the daily lives and traditional practices of its population. This research departs from the biographies of different families living in the districts of Maracanã and from my own experiences as an eventual dweller of the region. Then, I analyze the meanings of inhabiting places where the contexts of urban development and multiple devastations are present. These meanings are taken as outcoming from expanding urbanity and an advancing world that hesitates the possibilities of inter-knowledge and intersubjective trust. The reflections raised by my interlocutors make it evident the fears produced through relating. The obligations they comply with the catholic saints – which are expressed in the domestic space – potentially confront the fear of an urban violence to which the districts are associated when they dynamize a constrained spatiality. After all, it’s less likely that the fear of human actions domains us when the excess of religious happiness makes us feel like we’re in a good company